2023
DOI: 10.1590/1980-5373-mr-2022-0339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Argon Partial Pressure Variations on Wettability and Anti-icing Characteristics of Aluminum Doped ZnO Thin Films

Abstract: When ice forms on solid surfaces, it can cause issues in many different sectors (aircraft, electricity lines, etc.). Surfaces and coatings with hydrophobic qualities may be used in anti-icing applications. The purpose of this work is to utilize RF Magneton Sputtering to deposit AZO thin coatings, which will slow the accumulation of ice on the surface. The effects of changes in argon partial pressure on the anti-icing, wettability, optical, and structural properties of the resulting thin films have been experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…S. Han et al found that increasing the gas flow rate from 25 to 100 sccm reduced the roughness from 0.43 to 0.38 nm. Coating roughness was observed to be influenced by the flow rate and the size of the particles [43,44]. Higher deposition times result in progressively thicker coatings of chromium oxynitride.…”
Section: Hydrophobic Propertiesmentioning
confidence: 99%
“…S. Han et al found that increasing the gas flow rate from 25 to 100 sccm reduced the roughness from 0.43 to 0.38 nm. Coating roughness was observed to be influenced by the flow rate and the size of the particles [43,44]. Higher deposition times result in progressively thicker coatings of chromium oxynitride.…”
Section: Hydrophobic Propertiesmentioning
confidence: 99%
“…The use of coating technologies has the ability to confer a number of diverse characteristics and functions upon substrates. These characteristics and functions include anti-microbial qualities, hydrophobicity, and anti-icing capabilities [10,11]. As a consequence of this, development of multifunctional films and innovations, as well as their investigation and design have garnered a significant amount of attention and effort due to the economic value of these materials and the high demand that has resulted from the vast variety of uses the materials have.…”
Section: Introductionmentioning
confidence: 99%